Using after school programme to improve mathematics achievement and attitude among grade ten low achievers (2018)
Importance of mathematics in technological development of any nation requires that more attention be given to students with consistent failure in the subject. This study established the effectiveness of an after school programme among low learners in mathematics. Pre- and post-test, control group quasi-experimental design was used for the study. Participants (grade 10. ages 14-15 students) who scored 40% and below in the diagnostic assessment were selected across the four schools far the experiment. Two schools each were randomly assigned to control (conventional) and treatment (use of diagnostic assessment followed by the after school programme) groups. A total of 95 participants (49 males and 46 females) formed the sample far the study. Four research instruments were used. A t-test was used for the analysis. No significant difference in students ' achievement and attitude was evident before treatment; however, there was significant effect of treatment on students’ posttest mathematics achievement t(9S)=9.22, p<0.05 but not on attitude. Teachers are encouraged to use diagnostic assessment to identify students with learning needs and use after school programme to enhance their performance